PREVENTION OF OVARIAN CANCER - Irawan Sastradinata (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Ovarian cancer is a gynecological malignancy that in Indonesia still ranks third after cervical cancer and uterine corpus cancer 1. In the United States, ovarian cancer is the second most common gynecologic cancer and the leading cause of death from gynecological cancer. Clinically, its development is different from cervical cancer. Namely, ovarian cancer does not have apparent initial clinical symptoms, so that it is difficult to detect early. As a result, 65-75% of ovarian cancer are diagnosed at an advanced stage. Symptoms of ovarian cancer are non-specific, easy to miss in the early stages; symptoms are often seen in advanced stages (stage III or stage IV) a combination of a full stomach, bloating, nausea, abdominal distension, early satiety, fatigue, changes in bowel movements, urinary symptoms, back pain, dyspareunia, and weight loss. Preventive and promotive efforts in reducing the incidence of ovarian cancer are identified risk factors for ovarian cancer.